(3aj fSH YHO GdYXjes - (3GdWGdbGfj, CHh GdbGSe, GdUGMH, ESeGYjd Hf YHGO Hf GdYHGS, J (B385 (3g`s ((3MSf Hf YHO GdgGOj Hf ehSi GdehShj GdNQSGfjs)
(3ChdgG (B:s
(3bGd GdUGMH QMeg Gddg (B: (3oSFHJ Yf fSH YHO GdYXje GdMSjfj GdeOahf HGdTLQI UGMH GdeTNO bOS Gddg QhMg hMGdg hGYJbGOg hbOQ Ydeg hRgOg PGcQ Pdc Ydi GNJUGQ (B...s
(3BNQgG (B:s
.. (3abdJ (B: (3jQMec Gddg eG fOQj UMHJc EjGg aEf MOK HdG MOK aEdi ef ? abGd (B: (3Zf adGfG LeY GdbQBf hgh UGMHce hgh ceG SqQc (B. (3Je GdcJGHs
(3Yf fSNI GdSjO YHO GdQRGb GdehShjs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe (B1\316s
(3GdPQjYI (B16 -191 ( 1126 )s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
Keywords: (3GdJGQjNs